Wall climbing robot - Rahman, Md. Mozasser (2010)
The Robot, named as TRAIN WALL BOT, is designed which has the ability to navigate on smooth vertical surfaces with the capability to avoid obstacles and overcome it if the height of the obstacles is about 1cm. The design is inspired from train steel wheel movement which uses two actuated legs with rotary motion supplied from the motor. The Robot uses pneumatic system and the suction force is supplied by an air compressor that will turn on intermittently. The sucking system force controls the attachment of the robot to the wall by using 3 vacuum valves and 6 vacuum pads (2 vacuum pads on each leg, and 2 vacuum pads below the body). The robot is controlled using PIC16F877A. The main body of the robot carries the motor and important electronic components. Two limit switches are used to acknowledge the contact with its navigating surface, one is attached with one leg and other is attested with the body part. Vacuum suction is controlled based on the ON OFF priority of the limit switch. IR distance sensor detects obstacles which are higher than 1cm. The simple design of the Robot ensures the capability to walk, climb vertically up to 85º and 90º slope smooth surfaces and avoid obstacles. It has the advantages of faster forward and backward movements which is smooth and more stable (because of the coupling design)than other existing wall climbing Robots.